Study on solid waste generation, management and analysis in Kuantan - Amirul Aizzat, Zamani (2014)
Knowledge on solid waste generation, management and handling is necessary for an accurate decision making in the management strategy of urban waste. In Malaysia, the disposal of waste is under the legislation of Environmental Quality Act, 1974. The objective of this study are to investigate the solid waste generation and management within Taman Indera Sempurna, Kuantan, to investigate the level of recycling practice and awareness of its benefits and the importance among the residents at Taman Indera Sempurna, and to provide recommended solutions to improve solid waste management, handling and to promote recycling initiatives among the residents. This study also verifies the relationship of socio-economic status and lifestyles that influence the amount of waste generated along with their waste disposal behavior. A total of 50 copies of questionnaires will be handed to randomly selected residents regardless their race, age, education level and even their level of income. Judging by the study, both the solid waste management and handling in Taman Indera Sempurna can be classified as adequate. Awareness of recycling among the residents shows a moderately positive result where the respondents are able to acknowledge the benefits of recycling culture. The recommendations such as the establishment of solid waste recycle centre, the enforcement of law and reducing the usage of plastic bags have been made to boost the effectiveness and efficiency of current solid waste management, handling, and recycling as well.